Economic Valuation of Water in the High Basin of the Lerma River, Mexico - Aguilar-Sánchez, Genaro; De la Rosa-Mejía, Eduardo (Revista de Estudios Andaluces, 2018)
The objective of this paper is to estimate the willingness to pay (DAP) by the inhabitants of the municipality of Almoloya del Rio, state of Mexico in exchange for receiving a quality drinking water service, as well as the generation of actions for the conservation and recovery of bodies of water of the locality. For such purposes, the Contingent Valuation procedure has been used, which is based on the creation of a simulated market through surveys, which is ideal to estimate the economic value of a good that has no market, in this case the water service valued as a scarce and indispensable asset. The work concentrated field phase and the design of econometric models, applied to environmental assessment techniques, the Logit model of the SAS statistical program was used. As a result of the research, a considerably low DAP was obtained, which highlights the Income and Education variables, which were statistically significant.